Fancy a gene? A surprisingly complex evolutionary history of peroxiredoxins. - Zíková, Alena; Oborník, Miroslav; Lukeš, Julius (Shared Science Publishers, 2015)
While the phylum Apicomplexa includes “only” several thousand described species of obligatory parasites of animals, it may in fact be the most specious group of parasitic protists with over a million species [1]. The best known representatives are Plasmodium spp., Toxoplasma gondii and Cryptosporidium spp., which belong to the most important and widespread human parasites exacting an enormous disease burden. On the other hand, dinoflagellates and colpodellids, which are monophyletic with the apicomplexans, are ecologically highly significant, as they belong to the most abundant marine protists [2]. As the common ancestor of these groups was most likely a free-living photosynthesizing protist, one wonders, which evolutionary forces contributed to the dramatic transition of some of its descendants into the arguably most successful intracellular parasites? Although a range of various processes and mechanisms contributed to this transition, most likely it also involved an acquisition of genes via horizontal gene transfer (HGT), which might have provided typical characteristics of a parasitic cell, such as immune escape, nutritional dependence and the capacity to invade other cells.
Keywords: horizontal gene transfer; Apicomplexa; endosymbiont; Plasmodium; Chromera; peroxiredoxin; oxidative stress